Disinfection by-products in chlorinated drinking water and their potential health effects on humans : an international perspective - Siti Fatinah Afiqah Sukiman (School of Environmental Engineering University Malaysia Perlis, 2011)
The use of chlorine as a disinfectant in drinking water has resulted to chemical compounds known as disinfection by-products (DBPs). The present of these compound has become emerging issue due to its potential health effects on humans. To gauge the risk of DBPs on human health risk evaluation was carried out on selected compounds using cancer risk and probabilistic technique. 3-chloro-4-(dicholomethyl)-5-hydroxy-2(5H) furanone (MX) and N-nitrosodimethylamine (NDMA) were selected based on their potential health effects on humans. Concentration data from several countries covering both compounds were gathered from published literature. More than 80% of the concentration data for MX and NDMA were below the WHO guidelines value of 6.7 ng/L and 100 ng/L respectively.